التأديب دراسة فقهية قانونية مقارنة ضرب الزوجة والولد والتلميذ نموذجا - سوفلي, كمال (University of eloued جامعة الوادي, 2014)
ىيعرض ىذا البحث، إلى مكضكع التأديب بالضرب، في الكسط الأسرم كالمدرسي، حيث يتناكؿ مسألة تأديب الزكج زكجتو؛ مف الناحية الشرعية كالقانكنية؛ سكاء لحؽ ا﵀ تعالى أك لحؽ الزكج نفسو، كبياف الحدِّ الذم يصير فيو ىذا الحؽ يمجَّرما، يستكجب ج ا زء جنائيا شرعا كقانكنا، كما يتناكؿ مسألة تأديب الكالد كلده؛ سكاء كاف ممي ا ز، غير مميز أك بالغا؛ ث مسألة تأديب المعم تمميذه؛ لتعممو أك لأدبو، كبياف مسألة اشت ا رط الإذف في تأديبو، مع الكقكؼ عمى مكقؼ بعض التشريعات العربية، كبالأخص تشريعنا الكطني منو؛ كبياف حدكد كشركط الضرب في التأديب في كؿ ما سبؽ مف الحالات. Abstract This research tackles a very important topic, which is the domestic and school violence. Concerning the domestic violence, the research took the example of woman being exposed to violence by their husbands from the legitimate point view, whether that violence is for the sake of God’s right, or the husband’s own right. In addition to the justification of when the husband is considered as a guilty person, if it is so what does this deed entail in both legitimacy and law? Also another kind of domestic violence is tackled in this research, which is the punishment or violence from the father on his son, whether his son is mature or not. The other type of violence, which is the school one, the current research takes the example of teachers practicing violence on their students, whether that violence was for the sake of making him/her learn better, or to punish him because of his bad behavior. The research also will make a clear explanation about what the national legislation thinks about both kinds of violence mentioned above, besides this; the research will provide a detailed explanation about the limits and the criteria, and conditions which should be occurred in a certain action to decide whether we should take a violent punishment or not in the cases mentioned above.
شريعة وقانون
Keywords: التأديب الضرب/فقيية قانونية/الزوجة; Disciplinary beating/legal faqih/wife